2016
DOI: 10.1016/j.jhydrol.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of geology in the hydrological response of Mediterranean catchments prone to flash-floods: Regional modelling study and process understanding

Abstract: s u m m a r yIn this study, a regional distributed hydrological model is used to perform long-term and flash-flood event simulations, over the Cévennes-Vivarais region (south of France). The objective is to improve our understanding on the role played by geology on the hydrological processes of catchments during two past flash-flood events. This modelling work is based on Vannier et al. (''Regional estimation of catchment-scale soil properties by means of streamflow recession analysis for use in distributed hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 79 publications
0
24
0
2
Order By: Relevance
“…3.2, a probability of submersion is assigned to every road cut by combining the flooding susceptibility level of the road section and the return period of stream discharge in the river section. The CVN (Cevenne) distributed hydrological model (Vannier et al, 2016;Branger et al, 2010;Viallet et al, 2006) is used to compute the discharge at the 738 road cuts identified in the Alès case study in hourly time steps for the 2002 flash flood. The CVN model is especially developed for simulating hydrological responses in flash flood events in the Cévennes region (south of France).…”
Section: Road Network Sensitivity To Floodingmentioning
confidence: 99%
“…3.2, a probability of submersion is assigned to every road cut by combining the flooding susceptibility level of the road section and the return period of stream discharge in the river section. The CVN (Cevenne) distributed hydrological model (Vannier et al, 2016;Branger et al, 2010;Viallet et al, 2006) is used to compute the discharge at the 738 road cuts identified in the Alès case study in hourly time steps for the 2002 flash flood. The CVN model is especially developed for simulating hydrological responses in flash flood events in the Cévennes region (south of France).…”
Section: Road Network Sensitivity To Floodingmentioning
confidence: 99%
“…The high dynamics of karst systems have a great impact on flood hazard and drinking groundwater management. First, flash floods in streams are correlated to run-off on urban (Miller et al, 2014) or impervious geological surfaces, and increase in the Mediterranean environment due to the extreme Mediterranean rain-type (Merz and Bloschl, 2003;Nied et al, 2014) and karst contribution (Maréchal et al, 2008;Vannier et al, 2016). Second, the volume of groundwater discharged during floods represents a high recharge rate.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting perspective of this work would be the use of both Kf s maps in uncalibrated distributed hydrological models (see Vannier et al, 2016) to see if discharge simulation is improved at the regional scale.…”
Section: Discussionmentioning
confidence: 99%
“…This map was compared to the results obtained by Manus et al (2009) and Vannier et al (2016) using the Rawls and Brakensiek (1985) pedotransfer functions (RB85) over the area. For this mapping, these authors used a soil data base from the IGCS (Inventaire Gestion et Conservation des Sols, https://www.gissol.fr/tag/igcs) program, associated with a vector map of soil cartographic units at the 1/250000 scale (pedology map in the following discussion).…”
Section: Mapping Kf Smentioning
confidence: 99%
See 1 more Smart Citation